2014
DOI: 10.1186/1471-2164-15-546
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the evolutionary expansion of phosphorylation signaling networks using comparative phosphomotif analysis

Abstract: BackgroundProtein phosphorylation is catalyzed by kinases and is involved in the regulation of a wide range of processes. The phosphosites in protein sequence motifs determine the types of kinases involved. The development of phosphoproteomics has allowed the identification of huge numbers of phosphosites, some of which are not involved in physiological functions.ResultsWe developed a method for extracting phosphosites with important roles in cellular functions and determined 178 phosphomotifs based on the ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Here, we have determined the functions of phosphorylation signaling pathways in cellular processes. We have also investigated the relationships between 178 phosphomotifs and cellular functions, and evolutionary conservation [ 5 ]. Our analyses indicate that highly conserved phosphomotifs are likely to be involved in similar signaling networks with functionally important roles.…”
Section: Data Descriptionmentioning
confidence: 99%
See 3 more Smart Citations
“…Here, we have determined the functions of phosphorylation signaling pathways in cellular processes. We have also investigated the relationships between 178 phosphomotifs and cellular functions, and evolutionary conservation [ 5 ]. Our analyses indicate that highly conserved phosphomotifs are likely to be involved in similar signaling networks with functionally important roles.…”
Section: Data Descriptionmentioning
confidence: 99%
“…In a previous study, we identified 178 phosphomotifs [ 5 ] and investigated the evolutionary conservation of the phosphosites in each motif to elucidate the physiological roles of the identified motifs. To evaluate evolutionary conservation, we selected model organisms with rich genome information, as follows: Saccharomyces cerevisiae , Schizosaccharomyces pombe , Caenorhabditis elegans , Drosophila melanogaster , Danio rerio , Canis familiaris , Mus musculus , Pan troglodytes , and Homo sapiens .…”
Section: Data Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…These changes can regulate the catalytic activity of a phosphoprotein, thus, can either activate or inactivate them. Phosphorylation can also recruit neighboring proteins that recognize and bind phosphomotifs [ 37 , 38 ]. Since Pros is a phosphoprotein [ 29 ], we sought to re-examine the nuclear versus cytoplasmic localization and the phosphorylation status of Pros.…”
Section: Introductionmentioning
confidence: 99%